Dilution versus Solidification of Balanced Scorecard Projects: An Actor Network Theory Insight of Two Comparative Sri Lankan Case Studies - Gooneratne, T.N. (My University, 2007)
This study reports on two comparative case studies on the implementation of the Balanced Scorecard (BSC) in two Sri Lankan firms, referred to as Alpha and Beta. The purpose of the study is to carryout a background search of how the BSC message has reached the corporate sector of Sri Lanka, from a broader perspective, and more specifically to understand BSC practices in two organizational settings comparing their failures and successes. It deploys the qualitative method and the case study strategy, while the theoretical anchoring is provided by the Actor Network Theory and the Fabrication Model. The study illustrates that the BSC project of Alpha failed to get accepted as a useful Performance Measurement System, while the scorecard of Beta became accepted as important technique and got solidified at the organizational level due to different actors and their actions. xvi